O que os telejornais falam sobre Direitos Humanos? a importância de pensarmos a mídia jornalística numa perspectiva educacional - Oliveira, Flaviana de Freitas (Editora Oficina Universitária, 2022)
This book consists of a collection of scientific articles, elaborated throughout a research that sought to answer the following problem: how are Human Rights seen in the news programs of open broadcasters in Brazil? After carrying out an analysis of news programs from five Brazilian open channels, we came to the conclusion that television news does not address Human Rights and, when they do, it is not very educational. Human Rights Education, through the media, is not the only way to combat prejudice and concern, but it is an important way, as it has the capacity to reach a large part of the population. The absence of discussions on Human Rights contributes to people not knowing their rights and not being able to claim what is guaranteed to them.